The new politics of Indian gaming : the rise of reservation interest groups - Hansen, Kenneth N., 1967-; Skopek, Tracy A. (University of Nevada Press, 2011)
A collection of case studies outlines in detail the activities and results of lobbying and pressure groups on the state level regarding casinos on Indian land.